2011
DOI: 10.1186/cc10539
|View full text |Cite
|
Sign up to set email alerts
|

FIBTEM provides early prediction of massive transfusion in trauma

Abstract: IntroductionPrediction of massive transfusion (MT) among trauma patients is difficult in the early phase of trauma management. Whole-blood thromboelastometry (ROTEM®) tests provide immediate information about the coagulation status of acute bleeding trauma patients. We investigated their value for early prediction of MT.MethodsThis retrospective study included patients admitted to the AUVA Trauma Centre, Salzburg, Austria, with an injury severity score ≥16, from whom blood samples were taken immediately upon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
3
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(238 citation statements)
references
References 36 publications
3
221
3
11
Order By: Relevance
“…Mean Glasgow Coma Scale scores ranged from 11 to 14 but were reported in only six studies. [65][66][67][72][73][74] All studies [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] performed VE testing on admission. Three studies 64,71,72 evaluated TEG as a whole with a positive result based on a combination of different TEG parameters.…”
Section: Study Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean Glasgow Coma Scale scores ranged from 11 to 14 but were reported in only six studies. [65][66][67][72][73][74] All studies [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] performed VE testing on admission. Three studies 64,71,72 evaluated TEG as a whole with a positive result based on a combination of different TEG parameters.…”
Section: Study Detailsmentioning
confidence: 99%
“…Fifteen prediction studies [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] No multivariate analysis ED, emergency department; FAST, focused assessment for the sonography of trauma; ISS, injury sensitivity score; n, number enrolled; NR, not reported; PRBC, packed red blood cell. a Studies reported only as abstracts.…”
Section: How Well Do Viscoelastic Devices Predict Relevant Clinical Omentioning
confidence: 99%
See 1 more Smart Citation
“…Hypofibrinogenemia results not only from hemodilution by fluid supplementation to maintain blood pressure, but also from fibrinogenolysis due to hyperfibrinolysis induced by tissue‐type plasminogen activator released from injured endothelial cells 11. In this context, fibrinogen is the key molecule in trauma‐induced coagulopathy to be targeted for supplementation 12. Thus, early correction of hypofibrinogenemia would be a promising approach to prevent deadly coagulopathy and mortality after massive traumatic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Modificata da [11] ficazione del rischio di trasfusione massiva utilizzando i risultati disponibili entro 10 minuti dal tempo di coagulazione (FIBTEM® A10) [11]. Nella Figura 1 sono rappresentati i risultati del FIBTEM test: se la stabilità del coagulo dopo 10 minuti (A10) è maggiore di 8 mm all'ammissione in ospedale, il rischio di necessità di trasfusione massiva è abbastanza basso, pertanto dovrebbe essere evitato un trattamento proemostatico precoce e aggressivo; al contrario, in pazienti con stabilità del coagulo dopo 10 minuti (A10) inferiori a 8 mm o a 4 mm, il rischio di necessità di trasfusione massiva è molto alto: in questi casi il trattamento della coagulopatia dovrebbe essere iniziato precocemente per arrestare l' emorragia il più velocemente possibile (il cosiddetto approccio "Hit hard and early").…”
Section: Individuazione Dei Pazienti a Rischio E Delle Cause DI Sanguunclassified